Quantum Radar for Hidden Object Detection - Rahimi, Ramin; Reza, Ali; Hashemi, Fatemeh (Journal of Tecnologia Quantica, 2024)
Quantum radar is an innovative technology with great potential for detecting hidden objects with high precision. The background of this research is the need for technology that is able to detect objects behind material barriers with better accuracy than conventional radar, especially in search, rescue, and security applications. This study aims to evaluate the effectiveness of quantum radar in detecting hidden objects based on the type of barrier material, thickness, and detection distance. The research was conducted using an experimental method with a quantum radar prototype that was tested on various types of barrier materials, such as wood, concrete, and metal, in a controlled environment. Data is collected to evaluate the detection accuracy at a specific material thickness and the detection distance is between 1 to 7 meters. Quantitative analysis is used to identify patterns of relationships between material parameters, thickness, distance, and accuracy. The results show that quantum radar has the highest accuracy in wood materials with an accuracy rate of 89%, followed by concrete (78%), and metal (65%). The thickness of the material and the greater detection distance lead to a significant decrease in accuracy. The conclusion of this study indicates that quantum radar is effective for detecting objects behind non-conductive materials, but requires further development to overcome the weaknesses of reflective and long-range materials.